PEMBELAJARAN BAHASA JEPANG SEBAGAI SARANA PENDIDIKAN KARAKTER INSAN PARIWISATA INDONESIA - Rosita ' (Universitas Diponegoro, 2013)
Abstract Modernization of transport in the global era world allows people to travel to different countries of different cultures and languages ​​. Cross-cultural and language going on there . The important thing is the role of foreign language in the world is determined by the role of tourism in the cross-cultural and language . Related to that, foreign languages ​​are taught in vocational high schools and tourism majors in college . Japanese is one of the foreign language that is taught to students and student tourism. This is certainly due to considerations of the number of tourists from Japan after the fifth most tourists from Australia , Singapore , Malaysia , and China . In Management Studies Program Resort & Leisure ( Prodi MRL ) , one of the courses of tourism under the auspices of the Faculty of Social Sciences Education , UPI , the Japanese language is taught as an optional course in the semester 2, 3 , and 4 as 2 credits per semester . With a total of 6 credits , the Japanese language learning requires clear targets and careful planning . Additionally multidisciplinary tourism and growing demand for student learning Japanese tourism is always up to date . In this case , Prodi MRL makes monitoring activity on the job training as a means of evaluating and updating targets and plan learning Japanese . The results of these evaluations bring new ideas to direct learning towards character education for students , prospective human Indonesian tourism . Keywords: Japanese learning, character education, resort and leisure management